IMPLIKASI YURIDIS POST MERGER NOTIFICATION OLEH PELAKU USAHA DI INDONESIA - Suwinto Johan (Dialogia Iuridica, 2020)
Merger, consolidation, and acquisition of a company are normal activities for businessmen. These activities aims to maximize the value of company to shareholders. The implementation of merger, consolidation, and acquisition have the effect of creating a dominant position and monopolic practices, so those activities requires approval of a commission of business competition monitor. However, is the submission of approval done before or after the transaction made? Based on Undang-Undang Dasar No. 5 Tahun 1999, reporting has to do after transaction made according to criterias estabilished by government regulations. This research shows the effects of reporting after the transaction made. This research uses lex approach, case approach, and comparative approach. Comparative approach comparing lex in several countries. This research concludes that notification to KPPU must be made for transactions of a certain value, so as not to cause the effects of uncertainty and high transaction costs.